2014
DOI: 10.14507/epaa.v22.1693
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Educational Accountability in China and Denmark

Abstract: In recent decades, the concept of accountability has attracted more and more attention in public governance and management. The management of education is no exception. This article presents and discusses the evolution and current status of educational accountability in two different national contexts, China and Denmark. Two main sectors of education are covered, general school education and higher education. It is shown that both countries are marked by an increasing concern with educational accountability, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Smith's (2014) article places the logic of efficiency central in this role. Rasmussen and Zou (2014) make this point in their comparison of Chinese and Danish accountability, and Dorn (2014) sees the exercise of state power as inherent in the instrumental uses of testing. Ydesen and Andreasen (2014) make a slightly different point, seeing the roots of accountability in the budgetary notion of counting and also in the argument of New Public Management for transparency as a mechanism that is inherently democratic; although a very particular form of democracy not reconcilable with the notion of deliberative democracy.…”
Section: Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith's (2014) article places the logic of efficiency central in this role. Rasmussen and Zou (2014) make this point in their comparison of Chinese and Danish accountability, and Dorn (2014) sees the exercise of state power as inherent in the instrumental uses of testing. Ydesen and Andreasen (2014) make a slightly different point, seeing the roots of accountability in the budgetary notion of counting and also in the argument of New Public Management for transparency as a mechanism that is inherently democratic; although a very particular form of democracy not reconcilable with the notion of deliberative democracy.…”
Section: Themesmentioning
confidence: 99%
“…As Sobe and Boven (2014) and Smith (2014) point out in different ways, accountability is a discourse framework. That framework assumes comparisons between countries or schools should be a central focus of debate over education and culture policies of societies and states, as also demonstrated by Rasmussen and Zou (2014). In this way, accountability-regime discourse serves to license cultural critique of schools more generally and also legitimates specific state action.…”
Section: Themesmentioning
confidence: 99%
“…Responding to accountability discourses, researchers have reported theoretical debates around different forms of accountability, such as what forms of accountability ought to be considered over test-based accountability which has been dominant in education (e.g., Cranston, 2013;Fullan, Rincón-Gallardo, & Hargreaves, 2015;Sahlberg, 2007;Turnipseed & Darling-Hammond, 2015). In addition, researchers have empirically shown that there are multiple ways to achieve accountability across education systems internationally (e.g., Dorn & Ydesen, 2015;Klein, 2017;La Londe, 2017;Lim, 2016;Maroy, Pons, & Dupuy, 2017;Rasmussen & Zou, 2014;Thiel & Bellmann, 2017). Findings from these studies indicate that accountability policy implementation remains multifaceted depending on the context (Holloway et al, 2017;Klein, 2017), and therefore, the logics behind the implementation of accountability can differ based on historical backgrounds and structures of the education system.…”
Section: Introductionmentioning
confidence: 99%
“…The past two decades have witnessed increased accountability (Dorn and Ydesen 2014;Mattei 2012;Smith 2014), impacting schools across the globe and in a number of countries, including Australia (Lock and Lummis 2014), Canada (Jaafar and Anderson 2007), China (Rasmussen and Zou 2014), Denmark (Rasmussen and Zou 2014;Ydesen and Andreasen 2014), England (Glatter 2012), and Guinea (Dembélé and Schwille 2006). In the USA, the most recent iteration of accountability has come in the form of Race to the Top (RttT), a competitive grant program launched in 2009 that has prompted states to revamp their teacher evaluation models (U.S. Department of Education [USDOE] 2013), placing supervision and evaluation at the center of reform discourse and action.…”
Section: Introductionmentioning
confidence: 99%